DC MOTOR PID CONTROLLER WITH PWM FEEDBACK - Jotje Rantung; Hengky Luntungan (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2020)
This paper proposes a DC Motor PID controller with PWM feedback. Angular position control of DCmotor using pulse width modulation (PWM) feedback mechanism and Arduino microcontroller model of DC Motorare presented in this paper. To do this task, the followings are done. Firstly, a dynamic mathematical model of aDC motor is derived. Secondly, designing a control system to be applied to the DC motor. Thirdly, implementingthe hardware and software. The programming code for PWM signal execution is written by using c code andmatrix laboratory for Arduino microcontroller. The instruction code is implemented by the Arduinomicrocontroller to execute the control signal. Finally, the proposed DC Motor PID controller with PWM feedbackis proven by experimental. The experimental results show the effectiveness of a DC Motor PID controller withPWM feedback. The output can track the 260 rpm setpoint properly. The experimental results are not smooth dueto the noise in the system.Keyword: DC motor, PID controller, PWM, microcontroller